Lessons from forest decentralization: money, justice and the quest for good governance in Asia-Pacific. - Colfer, C.J.P.; Dahal, G.R.; Capistrano, D. (Earthscan, 2008)
The decentralization of control over the vast forests of the world is moving at a rapid pace with both positive and negative ramifications for people and forests themselves. Fresh research from a host of Asia-Pacific countries presents rich and varied experience with decentralization and provides important lessons for other regions. Beginning with historical and geographical overview chapters, the book proceeds to more in-depth coverage in the region's countries. Research findings stress rights, roles and responsibilities on the one hand, and institutions including organization, capacity building, infrastructure and legal aspects on the other. With these overarching themes in mind, the authors take on many controversial topics and address practical challenges related to financing and reinvestment in sustainable forest management under decentralized governance. Particular efforts have been made to examine decentralization at various scales from local to national and to address gender issues. The result is a unique examination of decentralization issues in forestry with clear lessons for policy, social equity, forest management, research, development and conservation in forested areas across the globe from the tropics to temperate regions